The Importance of Husband Support in Exclusive Breastfeeding: A Cross-Sectional Study - Anak Agung Sagung Mirah Prabandari; Maria Krishnandita; Suyasa Adryan Yunanda; Made Indra Wijaya (PT BMW Journal Sejahtera, 2024)
Introduction: Despite the significant benefits of breastfeeding, the proportion of exclusive breastfeeding in Indonesia remains low. Husbands, being one of the closest persons to breastfeeding mothers, might be an appropriate target for breastfeeding promotion. This study aims to investigate husband support in exclusive breastfeeding. Methods: A cross-sectional study was conducted in the working area of Dawan II Community Health Center from October to December 2018. Data was collected using questionnaires given to mothers with babies aged 6-24 months who had a husband. Analysis was performed using chi-square test and logistic regression on SPSS version 21. Results: The proportion of exclusive breastfeeding was 55.8%. Chi-square test revealed that husband support has a significant association with exclusive breastfeeding, with a PR of 3.6 (p<0.001; 95%CI= 1.48-8.73). Other associated variables were mother's educational level and parity. Multivariate analysis confirmed the association of husband's support with exclusive breastfeeding (AOR=14.22; p=0.004). Conclusion: Husband support is crucial in exclusive breastfeeding, and husbands should also be targeted for health promotion regarding exclusive breastfeeding.